Diary of a Minecraft Zombie : Zombie Goes to Camp - Book 6 - Zombie, Zach; Herobrine Publishing (New York, NY : Herobrine Publishing, 2015)
It could be the biggest challenge ever. Zombie prepares to go to Creepaway Camp, where camp counselors and cafeteria food could be terrifying.
"This unofficial Minecraft novel is an original work of fan fiction which is not sanctioned nor approved by the makers of Minecraft"--copyright page.
Keywords: Zombie, Zack -- (Fictitious character) -- Juvenile fiction; Minecraft (Game) -- Juvenile fiction; Zombies -- Juvenile fiction; Video game characters -- Juvenile fiction; Video games -- Juvenile fiction; Camps -- Juvenile fiction